Implikasi Pendidikan Agama Islam Berbasis Teknologi Informasi dan Komunikasi (Studi Kasus pada Siswa SMK Al-Huda): Implications of Islamic Religious Education Based on Information and Communication Technology (Case Study on Al-Huda Vocational School Students) - Riyan Hidayatulloh; Yuliyanti Yuliyanti (ITScience (Information Technology and Science), 2026)
The digital era of Society 5.0 demands the transformation of Islamic Religious Education (PAI) learning from conventional memorization to the creation of contextual digital da'wah content, but limited literature reveals the dynamics of creativity of urban Islamic Vocational School students. This study aims to describe the implementation of ICT-based Islamic Religious Education (PAI) learning and analyze its implications for the creativity of Al-Huda Kebon Jeruk Vocational School students through concrete manifestations of Blender 3D prayer videos, the